2008
DOI: 10.1111/j.1365-2486.2008.01591.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage, patterns and controls of soil organic carbon in the Tibetan grasslands

Abstract: The soils of the Qinghai-Tibetan Plateau store a large amount of organic carbon, but the magnitude, spatial patterns and environmental controls of the storage are little investigated. In this study, using data of soil organic carbon (SOC) in 405 profiles collected from 135 sites across the plateau and a satellite-based dataset of enhanced vegetation index (EVI) during 2001-2004, we estimated storage and spatial patterns of SOC in the alpine grasslands. We also explored the relationships between SOC density (so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
449
13
14

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 525 publications
(516 citation statements)
references
References 39 publications
40
449
13
14
Order By: Relevance
“…We found significant relationships between SOC density and nitrogen, bulk density, and soil texture (Table 6), which was consistent with other findings (Fu et al 2010;Lei et al 2013;Yang et al 2008). In this study, we found SOC density was significantly correlated with soil texture in the mineral horizon.…”
Section: Influencing Factors On Socsupporting
confidence: 82%
“…We found significant relationships between SOC density and nitrogen, bulk density, and soil texture (Table 6), which was consistent with other findings (Fu et al 2010;Lei et al 2013;Yang et al 2008). In this study, we found SOC density was significantly correlated with soil texture in the mineral horizon.…”
Section: Influencing Factors On Socsupporting
confidence: 82%
“…This is why a significantly negative correlation (r = −0.33, P < 0.01) is observed between MAT and SOCD (Table 3). By contrast, MAT higher than 4.6 • C may increase the vegetation productivity and thus contribute to increasing carbon inputs that override the temperature-induced rise in the soil decomposition rate (Yang et al, 2008). Our results confirm the observation made by Yang et al (2007) that the increasing trend of SOCD from the tropical to cold temperate zone in the eastern part of China is correlated with temperature.…”
Section: Relationships Between Soc and Climate Factorssupporting
confidence: 82%
“…A geostatistical approach was further used to map the regional pattern of SOC in different soil depth ranges. The method that was used for estimating the regional carbon pool in the present study is different from that used by Yang et al (2008), who estimated SOC storage by correlating SOC content with a remote-sensing vegetation index. Considering the rich ecosystem types of the Sanjiang Plain and coarseresolution remote-sensing imagery, this study used the kriging method to achieve a more accurate estimation of SOC than previous studies (Wang et al, 2002;Yu et al, 2007).…”
Section: Soc Estimates In the Sanjiang Plainmentioning
confidence: 99%
See 1 more Smart Citation
“…The total carbon stock of QinghaieTibetan peatlands was much smaller than that of boreal and tropical peatlands (Gorham, 1991;Page et al, 2011;Yu, 2012) and that of alpine grasslands on the same plateau (Wang et al, 2002;Yang et al, 2008). However, on the area basis, the carbon concentration of peatland is larger or comparable to the peatlands in other regions (Gorham, 1991;Page et al, 2011;Yu, 2012) and far larger than that in alpine grasslands (Wang et al, 2002;Yang et al, 2008).…”
Section: The Extent and Carbon Stock Of Peatlands On The Qinghaie Tibmentioning
confidence: 99%